Renal and axillary thrombosis in an infant of a diabetic mother - Tekinalp, Gülsevin; Oran, Olcay; Ertürk, Gülyüz; Yetgin, Sevgi (The Turkish Journal of Pediatrics, 1986)
Renal vein thrombosis is common in infants of diabetic mothers. Other lesions, such as gangrene of an extremity, have also been reported, but peripheral gangrene associated with renal vein thrombosis has rarely been seen. The case of an infant of a diabetic mother who presented in the immediate postpartum period with a gangrenous lesion of the right forearm and unilateral renal vascular thrombosis is presented.
Keywords: infant of diabetic mother; renal artery; thrombosis